Spectrophotometric Estimation of Sulfasalazine Via Oxidative Coupling Reaction Using 8-amino -2-naphthlene sulfonic acid and Potassium Periodate - Araw E. Ahmed; Khalida M. Omar (African Journal of Advanced Pure and Applied Sciences, 2023)
A simple, fast, and sensitive spectrophotometric technique has been proposed for the determination of sulfasalazine via oxidative coupling with 8_amino_2_naphthalene sulfonic acid reagent in the presence of potassium periodate as an oxidizing agent in the basic medium at room temperature to give stable yellow color dye with maximum absorption 457 nm. beer’s low is obeyed over the concentration range of 0.25-20 µg/ml of sulfasalazine in a final volume with the molar absorptivity of 2.9202×104 L.mol-1.cm-1 and Sandell,s sensitivity index 0.0136 µg/cm2. The proposed method was successfully s applied for the determination of sulfasalazine in pharmaceutical preparation (Tablets).